2012
DOI: 10.2987/12-6250r.1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Larvicidal Action, and Adult Repellency of Thymus magnus Against Aedes albopictus

Abstract: Thymus magnus, an endemic species, is found in the Republic of Korea. The volatile compounds extracted by SPME from T. magnus were investigated for their chemical composition and electrophysiological response against the Asian tiger mosquito, Aedes albopictus. The volatile compounds of T. magnus as determined by gas chromatography mass spectrometry were gamma-terpinene (33.0%), thymol (29.9%), beta-bisabolene (8.9%), p-cymene (8.3%), alpha-terpinene (5.0%), myrcene (4.7%), beta-caryophyllene (4.0%), alpha-thuj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thymol, as well as the majority of active compounds here reported, is occurring widely in several essential oils, especially Thymus, Monarda, and Origanum species, and it is well-known to contribute to the mosquito repellent and larvicidal activity of these oils. 7,35,36 On the other hand, the monoterpene umbellulone (which is the major constituent of U. californica essential oil) is less abundant in nature, and its biological activity as mosquito repellent and larvicidal activity are here reported for the first time. Umbellulone was found to act as a reversible Michael acceptor targeting the human and rat isoform of the nociceptive receptor TRPA1, 18,24 as well as other TRP receptors involved in chemosensation.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Thymol, as well as the majority of active compounds here reported, is occurring widely in several essential oils, especially Thymus, Monarda, and Origanum species, and it is well-known to contribute to the mosquito repellent and larvicidal activity of these oils. 7,35,36 On the other hand, the monoterpene umbellulone (which is the major constituent of U. californica essential oil) is less abundant in nature, and its biological activity as mosquito repellent and larvicidal activity are here reported for the first time. Umbellulone was found to act as a reversible Michael acceptor targeting the human and rat isoform of the nociceptive receptor TRPA1, 18,24 as well as other TRP receptors involved in chemosensation.…”
Section: ■ Introductionmentioning
confidence: 91%
“…In a study carried out with Thymus magnus oil, β-bisabolene showed 39.8% repellency against Aedes albopictus females, whereas β-caryophyllene showed 18% repellency, being the second-and third-most repellent compounds of the oil, respectively. (Park, Koo, Kim, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [39] reported that thymol and carvacrol elicited strong repellent activity for Tribolium castaneum (Herbst), a common stored-products insect pest, at 0.03 and 0.006 mg/cm 2 . Park et al [40] found that thymol and carvacrol had the lowest repellent concentration (RC) values against female adult Asian tiger mosquitos (Aedes albopictus) of the compounds identified in Thymus magnus. Thymol and carvacrol repellency have also been reported for the castor bean tick, Ixodes ricinus, and the poultry red mite, Dermanyssus gallinae [41,42].…”
Section: Eag Response Of Bean Bugsmentioning
confidence: 99%